Popliteal artery pseudoaneurysm due to femur exostosis. (January 2019) - Syed, Wahid; Bhat, Mohd Akbar; Ashraf, Hakeem Zubair; Ganie, Farooq; Ahmad, Feroze
Vascular complications of femur exostoses are rare, with popliteal pseudoaneurysm being the most common. After establishing the diagnosis, surgical treatment is mandatory. A 35-year-old woman presented with a painful pulsatile swelling in the lower medial aspect of the left thigh. Investigations revealed a pseudoaneurysm arising from the left popliteal artery adjacent to femur exostoses. Skeletal survey revealed multiple exostoses involving the upper and lower limbs. Surgical excision of the pseudoaneurysm was followed by ePTFE patch repair of the defect and excision of the exostoses. The patient was discharged after 5 days and followed up for 6 months with excellent results.